A Design Of Cellphone Charging Station System As Public Facility Using Off-Grid Solar Cell - Ahmad Daffa; Beni Satria; Solly Aryza (Jurnal Scientia, 2024)
Solar Power Plant (PLTS) is a more environmentally friendly generator, because this generator requires sunlight to be able to produce electrical energy. This PLTS is OFF-GRID so an energy storage place such as a battery is needed. The battery is also used to distribute electrical energy to the load where the load used is charging smartphones. And requires a solar charger controller that functions to regulate the electrical energy produced by the solar panel. This study analyzes the design of a smartphone charging station system as a public facility. In this test, 3 tests were carried out, namely testing how long it takes the battery to charge using solar panels, how long it takes the battery to discharge using a load, namely charging a smartphone, and conducting real-time testing by charging and discharging the battery together. The battery used has a total capacity of 12V 60Ah. In the battery charger testing method with a 100 WP solar panel, it takes 4 days, for the discharger testing using a load, it takes 6 days, and real-time testing shows that the output current fluctuates because the output current is very dependent on the intensity of sunlight that occurs when the solar panel charges the battery.